A genome‐wide association study identifies novel gene associations with facial skin wrinkling and mole count in Latin Americans. (5th July 2021) - Chen, Y.; André, M.; Adhikari, K.; Blin, M.; Bonfante, B.; Mendoza‐Revilla, J.; Fuentes‐Guajardo, M.; Palmal, S.; Chacón‐Duque, J.C.; Hurtado, M.; Villegas, V.; Granja, V.; et al.
Summary: Background: Genome‐wide association studies (GWASs) have identified genes influencing skin ageing and mole count in Europeans, but little is known about the relevance of these (or other genes) in non‐Europeans. Objectives: To conduct a GWAS for facial skin ageing and mole count in adults < 40 years old, of mixed European, Native American and African ancestry, recruited in Latin America. Methods: Skin ageing and mole count scores were obtained from facial photographs of over 6000 individuals. After quality control checks, three wrinkling traits and mole count were retained for genetic analyses. DNA samples were genotyped with Illumina's HumanOmniExpress chip. Association testing was performed on around 8 703 729 single‐nucleotide polymorphisms (SNPs) across the autosomal genome. Results: Genome‐wide significant association was observed at four genome regions: two were associated with wrinkling (in 1p13·3 and 21q21·2), one with mole count (in 1q32·3) and one with both wrinkling and mole count (in 5p13·2). Associated SNPs in 5p13·2 and in 1p13·3 are intronic within SLC45A2 and VAV3, respectively, while SNPs in 1q32·3 are near the SLC30A1 gene, and those in 21q21·2 occur in a gene desert. Analyses of SNPs in IRF4 and MC1R are consistent with a role of these genes in skin ageing. Conclusions: We replicate the association of wrinkling with variants in SLC45A2, IRF4 and MC1R reported in Europeans. We identify VAV3 and SLC30A1 as two novel candidate genes impacting on wrinkling and mole count, respectively. We provide the first evidence that SLC45A2 influences mole count, in addition to variants in this gene affecting melanoma risk in Europeans. Abstract : What is already known about this topic? A few loci have been associated with skin ageing features in Europeans, but most of these loci have not been replicated in independent studies. Previous studies have focused mainly on Europeans. What does this study add? We replicate the associations of MC1R, IRF4 and SLC45A2 with skin wrinkling in Latin Americans with Native American, European and African ancestry. We identify new wrinkling loci, including VAV3 . We report a novel association with mole count: SLC45A2, a known melanoma‐associated gene. What is the translational message? Our Euro‐centric scientific literature is skewed toward white populations, therefore providing only a restricted view of worldwide human diversity. This study reports genetic variations ( VAV3, SLC30A1 ) in Latin Americans of mixed continental ancestry, which associate with facial skin wrinkling and mole count, respectively. Moreover, a SLC45A2 single‐nucleotide polymorphism may also explain melanoma risk. This study may help in developing interventions for age‐associated loss of skin function and prevention of melanomagenesis. Linked Comment:  A.K. Langton and R.E.B. Watson. Br J Dermatol 2021; 185:883–884 .